Hubungan Iklim Organisasi dengan Organizational Citizenship Behavior (OCB) pada Karyawan Bank Nagari Kantor Pusat Padang - Ade, Frihapma Semita; Asry, Vadila Annisa; Syahrina, Isna Asyri (Psyche 165 Journal, 2023)
Productivity and effectiveness of the company to achieve a target or goal must have human resources or employees who can behave positively and can also create a good and comfortable atmosphere. The purpose of this study was to determine the relationship between organizational climate and organizational citizenship behavior (OCB) in Bank Nagari Employees, Padang head office. The independent variable in this study is organizational climate and the dependent variable is organizational citizenship behavior (OCB). The measurement tools used in this study are the organizational climate scale and the Organizational Citizenship Behavior (OCB) scale. The sampling technique is probability sampling. The sample in this study is based on the table from Issac and Michael with an error rate of 10%. So that the number of samples in this study were 130 people. The test results show that the validity coefficient on organizational climate moves from 0.403 to 0.849, while the reliability coefficient is 0.955, and the validity coefficient on Organizational Citizenship Behavior moves from 0.303 to 0.887, while the reliability coefficient is 0.941. Based on data analysis, a correlation value of 0.777 was obtained with a significance level of 0.000, which means that the hypothesis is accepted. This shows that there is a significant relationship between organizational climate and organizational citizenship Behavior of employees who work at Bank Nagari Padang Head Office. The effective contribution of organizational climate with organizational citizenship behavior for employees working at Bank Nagari Head Office is 60.5%.